Strain rebound and inhomogeneity in glass-to-metal seals: Radial vs axial strain evolution - Keqian Gong; Zheng Liu; Zifeng Song; Chao Zhou; Zhangjing Shi; Siyue Nie; Weisong Zhou; He Yan; Zhichun Fan; Yong Zhang (AIP Advances)
Glass, as a widely used amorphous material, often undergoes pre-stressing during processing to enhance its stability, with glass-to-metal (GTM) seal being a prominent example. Despite extensive studies on residual stress/strain in sealing glass, critical gaps remain in decoupling directional strains and understanding their in situ evolution during the cooling process, especially with respect to their microstructural origins. This study employs advanced fiber Bragg grating (FBG) in situ monitoring to decouple and independently analyze radial and axial strain evolution, providing novel insights into the mechanical anisotropy of sealing glass. The results revealed significant directional strain inhomogeneity throughout the cooling process, with strain evolution characterized by five distinct phases: zero-strain, rapid strain increase, gradual strain increase, significant strain rebound, and strain stabilization. Notably, axial strain froze earlier than radial strain (590 °C vs 575 °C): a counterintuitive finding attributed to free volume (FV) dynamics within the glass. Both directions exhibited pronounced strain rebound at lower temperatures, driven by the accumulation of smaller rebound events, effectively explained by FV theory. Moreover, the mismatch in thermal expansion coefficients between the glass and the metal housing significantly amplified radial strain, resulting in marked directional differences in strain behavior. Finite element analysis further corroborated these findings, confirming more pronounced variations in axial strain compared to the more uniform behavior observed in radial strain. These results underscore the anisotropic mechanical response of sealing glass within GTM seals, emphasize the value of FBG in situ monitoring for understanding strain evolution, and provide insights into enhancing the reliability of GTM seals across various applications.